Comparison of sampling leaf conventional and precision for micronutrients analysis in coffee crop - Carvalho, Luis Carlos Cirilo; Silva, Fábio Moreira da; Ferraz, Gabriel Araújo e Silva; Figueiredo, Vanessa Castro; Cunha, João Paulo Barreto (Coffee Science - ISSN 1984-3909, 2017)
One of the technologies that has been outstanding for the management of crops is the precision of coffee growing. However, there are still many fears on the part of growers in their adoption due to the lack of information to justify its use, compared to the current conventional management. This study aimed to evaluate the spatial and temporal variability of micronutrients (Zn, Fe, Mn, Cu and B) obtained through foliar analysis of a coffee plantation, allowing the creation of thematic maps in order to visualize their distribution in space. We also aimed to compare the results of precision coffee growing versus conventional management seeking to find results that justify its adoption in managing crops. The trial was carried out in Brejão farm, located in the municipality of Três Pontas - MG, in a coffee crop cultivate Topaz. Leaves were collected for foliar analysis according to two types of sampling: Precision coffee growing, with 100 collection points, and conventional management, dividing the area into two plots. The evaluations were performed at three different times: June / 2012, December / 2012 and June/2013. Through geostatistics, spatial and temporal variability of all variables was identified, enabling the creation of maps. For a given time, there are differences between the two types of management. In general, the accuracy of coffee allowed greater detail crop compared to the conventional management, allowing prevent management errors.